A mouse model for a partially inactive obesity-associated human MC3R variant - Lee, Bonggi; Koo, Jashin; Yun Jun, Joo; Gavrilova, Oksana; Lee, Yongjun; Seo, Arnold Y.; Taylor-Douglas, Dezmond C.; Adler-Wailes, Diane C.; Chen, Faye; Gardner, Ryan; Koutzoumis, Dimitri; Sherafat Kazemzadeh, Roya; et al. (Nature communications, 2016)
We previously reported children homozygous for two MC3R sequence variants (C17A+G241A) have greater fat mass than controls. Here we show, using homozygous knock-in mouse models in which we replace murine Mc3r with wild-type human ( MC3R hWT/hWT ) and double-mutant (C17A+G241A) human ( MC3R hDM/hDM ) MC3R , that MC3R hDM/hDM have greater weight and fat mass, increased energy intake and feeding efficiency, but reduced length and fat-free mass compared with MC3R hWT/hWT . MC3R hDM/hDM mice do not have increased adipose tissue inflammatory cell infiltration or greater expression of inflammatory markers despite their greater fat mass. Serum adiponectin levels are increased in MC3R hDM/hDM mice and MC3R hDM/hDM human subjects. MC3R hDM/hDM bone- and adipose tissue-derived mesenchymal stem cells (MSCs) differentiate into adipocytes that accumulate more triglyceride than MC3R hWT/hWT MSCs. MC3R hDM/hDM impacts nutrient partitioning to generate increased adipose tissue that appears metabolically healthy. These data confirm the importance of MC3R signalling in human metabolism and suggest a previously-unrecognized role for the MC3R in adipose tissue development. The melanocortin receptor, MC3R, regulates organismal energy homeostasis. Here, Lee et al . create knock-in mice with the a mutated version of the human MC3R receptor found in obese children, and show these mice have more fat and smaller bone, yet are by and large metabolically healthy.